A Case of Pancreaticopleural Fistula Causing Gross Right Hydrothorax (GAIMS Journal of Medical Sciences, 2023)
Hydrothorax due to a pancreaticopleural fistula (PPF) is an uncommon complication of acute pancreatitis. In patients with a history of pancreatitis, diagnosis is based on detection of amylase in the pleural exudate. For detection of pancreaticopleural disruption imaging, particularly magnetic resonance cholangiopancreatography (MRCP)is helpful. For management purpose invasive methods such as thoracocentesis and pancreatic duct drainage or pancreatic resection procedures are preferred. Here we are presenting a case of 40 years old male with pancreaticopleural fistula having right sided gross hydrothorax. Patient was managed conservatively.